Genome-Wide Analysis of Long Non-coding RNAs Involved in Nodule Senescence in Medicago truncatula - Yu, Lin; Huang, Tengda; Qi, Xinyu; Yu, Jingsu; Wu, Tian; Luo, Zupeng; Zhou, Lei; Li, Yixing (Frontiers in Plant Science, 2022)
Plant long non-coding RNAs (lncRNAs) are widely accepted to play crucial roles during diverse biological processes. In recent years, thousands of lncRNAs related to the establishment of symbiosis, root nodule organogenesis and nodule development have been identified in legumes. However, lncRNAs involved in nodule senescence have not been reported. In this study, senescence-related lncRNAs were investigated in Medicago truncatula nodules by high-throughput strand-specific RNA-seq. A total of 4576 lncRNAs and 126 differentially expressed lncRNAs (DElncRNAs) were identified. We found that more than 60% lncRNAs were associated with transposable elements, especially Helitron family. In addition, 49 DElncRNAs were predicted to be the targets of micro RNAs. Functional analysis showed that the largest sub-set of differently expressed target genes of DElncRNAs were associated with membrane component. Of these, nearly half genes were related to material transport, suggesting that an important function of DElncRNAs during nodule senescence is the regulation of substance transport across membranes. Our findings will be helpful for understanding the functions of lncRNAs in nodule senescence and provide candidate lncRNAs for further research.